COMPARISON OF SORGHUM GENOTYPES FOR FORAGE PRODUCTION AND QUALITY - M. Ayub; M. Khalid; M. Tariq; M. Elahi; M. A. Nadeem (Journal of Animal and Plant Sciences, 2012)
In the present study seven locally available advance lines of sorghum were investigated for their performance in term of forage material and nutritional profile of dry matter. The genotypes Hegari, Noor, F-214, JS-2002, F-207, PC-1 and F-9917 were compared in randomized complete block design. The significant variations in fresh and dry forage material as well as their nutritional values were noted among the genotypes. The genotype Hegari was the best performer for forage material and next to follow was Noor. The genotypes Hegari produced dry matter (22.53 t ha-1) with crude protein (8.29 %) and ash contents (9.60). Furthermore, its dry matter has the lowest value for crude fibre. The higher values produced by Hegari for more dry matter and nutritive values can be attributed to higher leaf area. The genotypes F-214 and F-9917 had been very poor for crude protein and ash contents, respectively. The genotype F-9917 must not be recommended for forage purposes due to its lower ash and higher crude fibre contents in dry matter. Taking a better variety in respect to dry matter and nutritional contents, the Hegari should be preferred over the tested varieties for forage purpose.
Keywords: Genotypes; Forage potential; Nutritional value